2023
DOI: 10.3390/v15051132
|View full text |Cite
|
Sign up to set email alerts
|

Booster Dose of SARS-CoV-2 mRNA Vaccine in Kidney Transplanted Patients Induces Wuhan-Hu-1 Specific Neutralizing Antibodies and T Cell Activation but Lower Response against Omicron Variant

Andrea Del Mastro,
Stefania Picascia,
Luciana D’Apice
et al.

Abstract: Kidney transplanted recipients (KTR) are at high risk of severe SARS-CoV-2 infection due to immunosuppressive therapy. Although several studies reported antibody production in KTR after vaccination, data related to immunity to the Omicron (B.1.1.529) variant are sparse. Herein, we analyzed anti-SARS-CoV-2 immune response in seven KTR and eight healthy controls after the second and third dose of the mRNA vaccine (BNT162b2). A significant increase in neutralizing antibody (nAb) titers were detected against pseud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…KTXRs are at a risk of severe SARS-CoV-2 infection because of their reduced T-cell immunity 43 . A previous study indicated that the third mRNA dose induced a T cell response against WT spike peptides in KTXRs, while cellular immunity toward Omicron BA.1 variant immunogenic peptides was low in both KTXRs and healthy controls 9 . However, no studies have evaluated the T-cell responses to Omicron BA.5 spike peptides.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…KTXRs are at a risk of severe SARS-CoV-2 infection because of their reduced T-cell immunity 43 . A previous study indicated that the third mRNA dose induced a T cell response against WT spike peptides in KTXRs, while cellular immunity toward Omicron BA.1 variant immunogenic peptides was low in both KTXRs and healthy controls 9 . However, no studies have evaluated the T-cell responses to Omicron BA.5 spike peptides.…”
Section: Discussionmentioning
confidence: 91%
“…KTXRs have more severe SARS-CoV-2 infection than healthy controls 3 7 . Furthermore, KTXRs have lower neutralizing antibody titers and cellular responses against B.1.1 (WT), B.1.617.2 (Delta), and B.1.1.529 (Omicron BA.1) after SARS-CoV-2 vaccination than healthy controls 8 , 9 . However, to our knowledge, few studies have evaluated neutralizing antibodies and cellular responses against Omicron BA.5 in KTXRs.…”
Section: Introductionmentioning
confidence: 99%
“…However, considering the potential for immune tolerance and exhaustion in cellular immunity after repeated mRNA vaccine administration (especially five or more doses), there might be an alternative strategy for SARS-CoV-2 immunization. The potential evasion of cellular immune responses to VoCs following the emergence of the Omicron variant ( 30 ) further emphasizes the need to re-evaluate vaccination strategies for high-risk groups. Thus, a booster with the monovalent vaccine targeting the latest VoC may be beneficial to avoid the suppression of cellular immune response observed in the part of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…KTXRs have more severe SARS-CoV-2 infection than healthy controls [3][4][5][6][7] . Furthermore, KTXRs have lower neutralizing antibody titers and cellular responses against B.1.1 (WT), B.1.617.2 (Delta), and B.1.1.529 (Omicron BA.1) after SARS-CoV-2 vaccination than healthy controls [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%